2016
DOI: 10.18848/2325-162x/cgp/v10i03/17-45
|View full text |Cite
|
Sign up to set email alerts
|

The Lens of the Lab: Design Challenges in Scientific Software

Abstract: Playful and gameful design could improve the quality of scientific software. However, literature about gamification methods for that particular type of software is presently scarce. As an effort to fill that gap, this paper introduces a set of design challenges and opportunities that should be informative to professionals approaching the area. This research is based on literature review on scientific software development, also contemplating material on the gamification of science, software, and work. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 131 publications
(201 reference statements)
0
7
0
Order By: Relevance
“…The Software Citation Group has published the Software citation principles in 2016 7. The group is now closed and has evolved to the Software Citation Implementation Working Group 13 . They are specialized communities, focusing on the particular issue of software citation.…”
Section: A Snapshot On the International Rs Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…The Software Citation Group has published the Software citation principles in 2016 7. The group is now closed and has evolved to the Software Citation Implementation Working Group 13 . They are specialized communities, focusing on the particular issue of software citation.…”
Section: A Snapshot On the International Rs Landscapementioning
confidence: 99%
“…Reviewer Expertise: computer science, robotics,mathematics I confirm that I have read this submission and believe that I have an appropriate level of expertise to confirm that it is of an acceptable scientific standard. 13 September 2019 Reviewer Report https://doi.org/10.5256/f1000research.21946.r53711 1.…”
Section: Open Peer Review Current Peer Review Statusmentioning
confidence: 99%
“…1) authors consider scientific software as the one widely used in science and engineering fields. More precisely, in 16 (see also the summarized version in 17), we can find the following definition:…”
Section: Research Software: Definition Publication and Citationmentioning
confidence: 99%
“…Although we think that software development skills have improved in the last decades in the scientific community, and more and more research software developments arise from well-organized teams with well-established testing, management, documentation and dissemination procedures, the paradigmatic model that we have here in mind is one that we feel it is still largely present 12, 16, 17, 20: software that is developed by small (perhaps international) teams, or individually, usually with few development skills, where the main goal is the research activity itself. That is, software that mainly aims to give correct scientific results of whatever kind 18, 21 and not necessarily a sound software “product”, well documented, tested, easily reusable or maintained.…”
Section: Research Software: Definition Publication and Citationmentioning
confidence: 99%
“…Current literature has indicated that the software product selection and usage are parameters that can influence the course of a research undertaking and, as such, there is a requirement for systematic reviews of the software output as well as careful analysis of the context within which the software product is employed (Lutters & Seaman, 2007;Joppa et al, 2013;Zacharia et al, 2015;Queiroz & Spitz, 2016).…”
Section: Responsibility In Comprehensionmentioning
confidence: 99%